Education on the Utilization of Family Medicinal Plants to Support Promotive and Preventive Family Health in Rawang Subdistrict - Dian Ayu Juwita; Hansen Nasif; Wira Sanjaya; Rahmah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2026)
Family Medicinal Plants (Tanaman Obat Keluarga/TOGA) have considerable potential to support promotive and preventive family health. However, limited community knowledge regarding their benefits, proper utilization, and safety often hinders optimal use at the household level. This community service activity aimed to provide education on the utilization of TOGA to support family health. A community-based educational program with a one-group pre-test and post-test design was conducted in Rawang Subdistrict on 17 August 2024, involving 30 participants. Educational sessions were delivered through interactive lectures and discussions covering the benefits, methods of use, and safety aspects of TOGA. Participants’ knowledge was assessed using a structured questionnaire administered before and after the intervention, and data were analyzed descriptively. The pre-test results indicated moderate to low baseline knowledge. Following the intervention, participants’ knowledge improved significantly, with mean scores increasing from 56.3% to 82.1% (an increase of 25.8 percentage points). The greatest improvements were observed in understanding preparation methods and safety considerations. These findings demonstrate that TOGA-based education effectively enhances community knowledge in supporting promotive and preventive family health. Integrating such educational programs into community health initiatives is essential to strengthen family-level health promotion and disease prevention.